Lotfi Zadeh: the genius creator of fuzzy logic (Publicaciones en Ciencias y Tecnología, 2018)
Lotfi Asker Zadeh: mathematician, electrical engineer, computer scientist and Iranian-American professor at the University of California in Berkeley. He created the theory of fuzzy sets and fuzzy logic. Zadeh is one of the most remarkable geniuses of the current era. Among his other creations are the Z-transform method, the approach of the theory of linear systems based on states, linguistic variables, fuzzy control, approximate reasoning, theory of possibility, "soft computing", computation with words, computational theory of perceptions, theory of the granulation of fuzzy information, generalized theory of uncertainty, and Z-numbers.
Keywords: Zadeh; fuzzy sets; fuzzy logic; generalized theory of uncertainty; Z-number; fuzzy